Product Quality Control In CV XYZ Using Seven Tools and Quality Control Circle - Priyo Sambodo; Atikha Sidhi Cahyana (Procedia of Engineering and Life Science, 2022)
In the industrial world, competition for technological advances and marketing strategies is a very big thing, with the level of In this competition, business people are required to always innovate and implement the best strategies to improve product quality or quality. The purpose of this study was to identify the most dominant product defects of the active speaker production process at CV. XYZ. The method used is Seven Tools and Quality Control Circle (QCC) to identify and evaluate the potential failure of the product in CV. XYZ. the Quality Control Circle (QCC) method by applying the PDCA (Plan-Do-Check-Action) and with the Seven Tools (Stratification, Histogram Graph, Pareto Chart, Cause-Effect Diagram, Control Graph). The results of the study indicate that the known factors causing product defects that can be seen from fishbone are humans, machines, materials, environment, and methods and provide suggestions for improvements that are implemented using PDCA (Plan-Do-Check-Action) which can minimize the occurrence of defects. repeated.